Positron emission tomography with α‐[11C]methyl‐l‐tryptophan in tuberous sclerosis complex–related epilepsy. Issue 12 (28th October 2013) - Rubí, Sebastià; Costes, Nicolas; Heckemann, Rolf A.; Bouvard, Sandrine; Hammers, Alexander; Martí Fuster, Berta; Ostrowsky, Karine; Montavont, Alexandra; Jung, Julien; Setoain, Xavier; Catenoix, Hélène; Hino, Keiko; et al.
Summary Objective Tuberous sclerosis complex (TSC) is often associated with cerebral tubers and medically intractable epilepsy. We reevaluated whether increased uptake of α‐[11C]methyl‐l‐tryptophan (AMT) in cerebral tubers is associated with tuber epileptogenicity. Methods We included 12 patients (six male, 4–53 years old) with TSC and refractory seizures who were evaluated for epilepsy surgery in our center, including video‐electroencephalographic (EEG) monitoring, fluid‐attenuated inversion recovery magnetic resonance imaging (FLAIR MRI), and positron emission tomography (PET) with α‐[11C]methyl‐l‐tryptophan (AMT‐PET). Nine of these 12 patients also underwent intracerebral EEG recording. AMT uptake in each tuber was visually evaluated on PET coregistered with MRI. An AMT uptake index based on lesional/healthy cortex ratio was also calculated. Sensitivity and specificity values of AMT‐PET in the detection of epileptogenic lesions were obtained, using the available electroclinical and neuroimaging evidence as the gold standard for epileptogenicity. Results A total of 126 tubers were identified. Two of 12 patients demonstrated a tuber with clearly increased AMT uptake, one of whom also showed a subtle increased AMT uptake in another contralateral tuber. Four other patients showed only subtle increased AMT uptake. The only two tubers with clearly increased AMT uptake proved to be epileptogenic based on intracerebral EEG data, whereas none of the tubers associated with subtle increased AMT uptake were involved at ictal onset. In a per‐patient approach, this yielded a sensitivity of clearly increased AMT uptake in detecting tuber epileptogenicity of 17% (2/12 patients), whereas the per‐lesion sensitivity and specificity were 12% (95% confidence interval [CI]: 3–34%) and 100% (95% CI: 97–100%), respectively. Significance AMT‐PET is a specific neuroimaging technique in the identification of epileptogenic tubers in TSC. Despite its low sensitivity, the clinical usefulness of AMT‐PET still deserves to be considered according to the challenging complexity of epilepsy surgery in tuberous sclerosis.